A New Workflow for Whole‐Genome Sequencing of Single Human Cells. Issue 10 (18th August 2014) - Binder, Vera; Bartenhagen, Christoph; Okpanyi, Vera; Gombert, Michael; Moehlendick, Birte; Behrens, Bianca; Klein, Hans‐Ulrich; Rieder, Harald; Ida Krell, Pina Fanny; Dugas, Martin; Stoecklein, Nikolas Hendrik; Borkhardt, Arndt
<x xml:space="preserve">Abstract</x> Here, we present a new workflow combining an efficient adapter‐linker PCR‐based WGA method with 2nd generation sequencing. Amplification recovered up to 74% of the human genome. Copy number variants (CNVs) and loss of heterozygosity (LOH) detected in single cell genomes showed concordance of up to 99% to pooled gDNA. Allele frequencies of mutations could be determined accurately due to an allele dropout rate of only 2%. Sequencing with paired end reads allowed genome‐wide analysis of structural variants (SVs). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>